PENGARUH PERSEPSI TREND MAKE UP DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI MEA DACOSTA TULUNGAGUNG - Kusumaningrum, Angella Putri; Ekbal Santoso (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
In the midst of the rapidly growing make-up service industry, customer satisfaction has become a crucial factor in business success. Customer perception of constantly changing make-up trends and the quality of services provided are key aspects in maintaining customer loyalty. This study aims to examine the influence of make-up trend perception and service quality on customer satisfaction at Mea Dacosta Tulungagung. This research employed a quantitative approach using survey methods by distributing questionnaires to 120 customers as respondents. Data were analyzed using multiple linear regression assisted by SPSS version 26. The results showed that both partially and simultaneously, make-up trend perception (X1) and service quality (X2) have a significant influence on customer satisfaction (Y), with significance values less than 0.05. Simultaneously, the two independent variables also have a significant effect on customer satisfaction with a significance value of 0.000. The regression equation obtained is Y = 3.123 + 0.765X1 + 0.184X2. The Adjusted R Square value of 0.930 indicates that 93.0% of customer satisfaction variation can be explained by make-up trend perception and service quality variables, while the remaining 7.0% is influenced by other variables outside this study.